2015
DOI: 10.1097/mpa.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Ameliorates Experimental Severe Acute Pancreatitis via Enhancing Immunoregulation of CD4+ CD25+Regulatory T Cells

Abstract: Modulating immunoregulation of CD4 CD25 Treg is a critical mechanism for nicotinic anti-inflammatory pathway and it may be feasible to use selective agonists as an immunotherapy for SAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
1
22
1
1
Order By: Relevance
“…A more recent report confirmed that Tregs could specifically suppress cytotoxic T cell response [10], which was very important in pancreas tissue destruction of chronic pancreatitis patients [9]. The suppressive effects of Tregs on cytotoxic T cells were IL-10 dependent [10, 26]. Similarly, in our study, we found that decreased Tregs in chronic pancreatitis mice (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…A more recent report confirmed that Tregs could specifically suppress cytotoxic T cell response [10], which was very important in pancreas tissue destruction of chronic pancreatitis patients [9]. The suppressive effects of Tregs on cytotoxic T cells were IL-10 dependent [10, 26]. Similarly, in our study, we found that decreased Tregs in chronic pancreatitis mice (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…These findings are in sharp contrast to the overwhelming data supporting an independent effect of smoking and pancreatitis development (33,51,61,63,71,92,107,108,125,126). In this study the authors reason that potential racial differences in nicotine metabolism and susceptibility to smoking between the Taiwanese populations they examined versus ethnically different populations from the other investigations, may account for the discrepancy.…”
Section: Role Of Tobacco In Development Of Pancreatic Disease: Pancrecontrasting
confidence: 56%
“…Although these studies imply tobacco use potentiates alcohol effects in pancreatitis convincing data has emerged from several casecontrol and cohort studies strongly supporting an independent association between smoking and pancreatitis (33,51,61,63,71,92,107,108,125,126). The major findings from these studies are detailed in Table 1.…”
Section: Role Of Tobacco In Development Of Pancreatic Disease: Pancrementioning
confidence: 89%
See 2 more Smart Citations